Pendugaan Komponen Ragam Genetik dan Heritabilitas pada Populasi Tanaman F2 Cabai Rawit Hasil Persilangan Capsicum frutescens L. x Capsicum annuum L. - Abdul Hakim; Indra Permana; Anita Dwy Fitria (Vegetalika, 2026)
The development of superior varieties requires accurate genetic information, especially on the traits that will be used as selection criteria. Variance components (genetic variance, environmental variance, and phenotype variance) and heritability values are the genetic information for the selection process. Selection will generally be effective if the characters used as selection criteria have heritability values that are included in the high category (> 50%). The objective of this research for estimating the components of variance and heritability in a broad sense for a number of agronomic characters in the second generation (F2) population of cayenne pepper from the hybridization between Capsicum frutescens L. and Capsicum annuum L.  The genetic materials consisted of two parental lines, P1 (Bonita IPB) and P2 (Perisai IPB), each represented by 20 individual plants, and 150 individuals from the F2 generation. Estimation of variance components and broad-sense heritability was performed using the Mahmud–Kramer method. The results of the study showed that the diversity in the F2 population was higher than in both parents. This is indicated by the variance values for all characters being greater than both parents. Traits such as plant height, canopy width, stem diameter, day of flowering, fruit weight per plant, number of fruits per plant, fruit weight, fruit length, and fruit diameter showed high heritability values, while day of harvesting showed moderate heritability. These heritability estimates suggest that effective selection can be focused on traits with high heritability, thereby increasing selection efficiency and enabling favorable genetic progress in subsequent generations.